From changeling to citizen: learning disability and its representation in museums - Allday, Kathy (Museum and Society, 2015)
This paper examines why museums, both currently and historically, have excluded material relating to people with intellectual impairments. The national picture is examined briefly before the focus shifts to three UK museums in York, Leeds and Colchester where curatorial attitudes to including and presenting material on learning disability are compared and contrasted. Curatorial anxieties about the subject, a lack of national guidance on how to address learning disability in museum collections and displays and the elusive nature of available sources of material appears to discourage museums addressing the issue. Nevertheless, a few examples show that with organizational and professional commitment and the adoption of facilitative and consultative approaches, museums can present the history of learning disability in exciting and thought provoking ways that challenge pre-conceptions about intellectually impaired people. Given museums’ responsibilities under the Disability Discrimination Act (2005), the significance of the social inclusion agenda and calls for new museological practices, there has never been a better time for museums to reevaluate their approaches to learning impairment.